The practice of virginity testing in South Africa : a constitutional and comparative analysis - Rakubu, Motlalepula (My University, 2019)
In South Africa, the concept of virginity testing has been under the spotlight because of the Children’s Act 38 of 2005 partially legalising it. Section 12 thereof, provides for the testing to be performed on both male and female children over the age of sixteen with their informed consent. It has also been revived as a Zulu custom which gained momentum in response to the HIV/AIDS pandemic. This custom is, however, in contrast to the approach highlighted in the Act, since it targets only the girl child and mostly without her informed consent. Although a girl’s virginity is said to bring honour to her family, it also comes with inherent risks, since, in African societies, the myth that sex with a virgin, or a girl-child can cure AIDS, is prevalent. This dissertation examines, from a human rights perspective, the concept of virginity testing and related procedures/ provisions, the role and function of the virginity testers, as well as expectations/experience of the participants (the girls tested). The study asserts that the practice of virginity testing is a violation of human rights, strips the girl of her dignity, represents an invasion of bodily privacy and leads to degradation and humiliation. Virginity testing, according to this study, leads to limitation of rights and unfairly discriminates against the girls tested and cannot be justified in terms of the limitation clause, as provided by section 36 of the Constitution of the Republic of South Africa, 1996. As part of the comparative study, the analysis of the position in Senegal, regarding the successful abolishment of a similar discriminatory cultural practice, provides lessons on how both the South African government and NGO’s can work towards law reform in order to address the problem of virginity testing.
Thesis (LLM. (Development and Management Law)) -- University of Limpopo, 2019
Keywords: Virginity testing; Human rights; Teenagers; HIV/AIDS pandemic; Virginity -- Social aspects -- South Africa; Teenagers -- Sexual behavior -- South Africa; HIV infections -- South Africa -- Prevention